Maternal risk factors and early neonatal outcome among late preterm and term neonates in a neonatal intensive care unit in Punjab, India - T., Kambiakdik; Leelalanslat, Anish D.; Sohi, Inderpreet; Varkey, Varughese P. (International Journal of Contemporary Pediatrics, 2018)
Background: Late preterm neonates (34 to 36 weeks 6/7 days) were considered as ‘near term’ as they appeared apparently mature and comparable to term neonates. Many studies have now reported significantly higher rates of morbidity and mortality among this group of neonates. This study aims to evaluate the maternal risk factors associated with and short-term outcome of late preterm neonates compared to term neonates. Methods: A Retrospective cohort study was conducted in the Neonatal Intensive Care Unit of a tertiary care teaching hospital. All intramural late preterm neonates with gestational age of 34-36 weeks born during the study period were enrolled. The control group included term neonates (37-42 weeks) born during the study period. Data regarding the maternal risk factors and neonatal outcomes for both the late preterm and term neonates were collected from records maintained in the NICU. Results: There were 3275 deliveries during the study period, of which 2447 (74.8%) were term. Among the 828 preterm neonates, 500 (60.4%) were late preterms. The maternal risk factors significantly associated with late preterm neonates were PIH, eclampsia, APH, multiple gestation, PROM, oligohydramnios and abnormal dopplers. Incidence of Respiratory distress syndrome (RDS), sepsis and hypoglycemia were higher among the late preterm group with an odd’s ratio of 56.01, 9.9 and 7.8 respectively. Incidence of hypocalcemia, seizures and Persistent Pulmonary Hypertension (PPHN) were also higher among this group. There was no statistically significant difference in mortality among the two groups. Conclusions: Late preterm neonates have a significantly higher neonatal morbidity compared to term neonates.